1990
DOI: 10.1007/bf00712848
|View full text |Cite
|
Sign up to set email alerts
|

Picomolar-affinity binding and inhibition of adenylate cyclase activity by melatonin in syrian hamster hypothalamus

Abstract: 1. The effect of melatonin on forskolin-stimulated adenylate cyclase activity was measured in homogenates of Syrian hamster hypothalamus. In addition, the saturation binding characteristics of the melatonin receptor ligand, [125I]iodomelatonin, was examined using an incubation temperature (30 degrees C) similar to that used in enzyme assays. 2. At concentrations ranging from 10 pM to 1 nM, melatonin caused a significant decrease in stimulated adenylate cyclase activity with a maximum inhibition of approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

1991
1991
2015
2015

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 17 publications
0
9
0
Order By: Relevance
“…Indeed, the MBH seems to be a target for melatonin, as reported in the Introduction (9,11,35). It has been suggested that the inhibitory effect of melatonin on forskolin-stimulated adenylate-cyclase activity in hypothalamic homogenates could be mediated by melatonin binding sites (36).…”
Section: Discussionmentioning
confidence: 91%
“…Indeed, the MBH seems to be a target for melatonin, as reported in the Introduction (9,11,35). It has been suggested that the inhibitory effect of melatonin on forskolin-stimulated adenylate-cyclase activity in hypothalamic homogenates could be mediated by melatonin binding sites (36).…”
Section: Discussionmentioning
confidence: 91%
“…As determined by cAMP direct immunoassay, the higher 2500 μ m melatonin dose was able to decrease cAMP concentration, and this effect was abolished by luzindole, which increased cAMP in the presence of melatonin but not when administered alone. It has been shown that melatonin inhibits activity of adenylyl cyclase in a dose‐dependent manner [44]. Previous studies have indicated that the coupling of both MT1 and MT2 receptors seem to be necessary to inhibit adenyl cyclase when melatonin is administered at low doses [45].…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin also has long established inhibitory effects on the adenylate cyclase -cyclic AMP pathway (Niles and Hashemi, 1990;Niles et al, 1991;Vanecek, 1998), with consequent suppression of cAMP response element binding protein (CREB) phosphorylation (Kopp et al, 1997;von Gall et al, 2000). However, some of melatonin's actions are receptor-independent, involving interactions with intracellular targets including calmodulin, protein kinase C and nuclear receptors such as the retinoid Z receptor/retinoid acid receptor-related orphan receptor (RZR/ROR) (Agez et al, 2007;Carlberg, 2000;Luchetti et al, 2010;Soto-Vega et al, 2004).…”
Section: Introductionmentioning
confidence: 98%